Identifying failure factors due to corrosion erosion on pressured steam pipe elbow in geothermal power plant - Muda, Iskandar; Widyanto, Bambang (Eastern-European Journal of Enterprise Technologies, 2024)
This paper presents the findings of a corrosion erosion failure analysis of elbow pipe materials used to flow high-pressure water from underground. The failed elbow pipe material was above the wellhead forming a straight line in the longitudinal direction with a pipe length of 6200 feet below the ground surface. The working fluid in the elbow pipe was 25 % steam and 75 % water, flowing in the elbow pipe with a media flow rate of 180 tons per hour, a pressure of 22 bar, and a temperature of 220 °C. Elbow tubes were made of low carbon steel with Standard ASTM A234 having an outer diameter of 304.8 mm and a wall thickness of 9.271 mm. Macroscopic testing, chemical composition analysis, metallographic testing, hardness testing, X-ray diffraction testing, SEM, and EDS are a few of the test types conducted. The study’s findings showed that the elbow tubes experienced a thinning process on the inner wall of the outer curvature side with a rough and wavy surface texture or appearance. This type of failure is known as erosion-corrosion. The level of erosion-corrosion failure that occurs is greatly influenced by the pH of the fluid being flowed reaching 2.67–2.91, this is due to the very high Cl- of 1290 ppm, so the higher the rate of erosion-corrosion that occurs. These materials are the most popular and widely used in the oil and gas sector. However, this pipe has weaknesses because it is susceptible to erosion-corrosion Therefore, it is very important to choose the right material, namely, a material that is resistant to erosion-corrosion